2018
DOI: 10.1038/s41374-017-0009-0
|View full text |Cite
|
Sign up to set email alerts
|

β-Ecdysterone protects SH-SY5Y cells against β-amyloid-induced apoptosis via c-Jun N-terminal kinase- and Akt-associated complementary pathways

Abstract: Recently, the significantly higher incidence of Alzheimer's disease (AD) in women than in men has been attributed to the loss of neuroprotective estrogen after menopause. Does phytoestrogen have the ability to protect against amyloid-β (Aβ) toxicity? The aim of this study was to evaluate hypothesis that β-ecdysterone (β-Ecd) protects SH-SY5Y cells from Aβ-induced apoptosis by separate signaling pathways involving protein kinase B (Akt) and c-Jun N-terminal kinase (JNK). Here, we demonstrate that phytoestrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 46 publications
(78 reference statements)
1
27
0
Order By: Relevance
“…14 A recent study reported that βEcd possesses multiple pharmacological actions, including protection against β-amyloid-induced apoptosis. 15,16 Previously, βEcd was shown to increase the differentiation of mesenchymal progenitor cells towards osteoblasts in vitro, which is consistent with the observation of an increased osteoblast surface following in vivo βEcd treatment. 17 In the present study, hBMSCs were cultured with different concentrations of βEcd, and βEcd at 0, 25 and 50 μmol/l had no significant inhibitory effect on hBMSC viability.…”
Section: Discussionsupporting
confidence: 80%
“…14 A recent study reported that βEcd possesses multiple pharmacological actions, including protection against β-amyloid-induced apoptosis. 15,16 Previously, βEcd was shown to increase the differentiation of mesenchymal progenitor cells towards osteoblasts in vitro, which is consistent with the observation of an increased osteoblast surface following in vivo βEcd treatment. 17 In the present study, hBMSCs were cultured with different concentrations of βEcd, and βEcd at 0, 25 and 50 μmol/l had no significant inhibitory effect on hBMSC viability.…”
Section: Discussionsupporting
confidence: 80%
“…Although AD is the most prevalent neurodegenerative disease, affecting over 47 million people globally, no satisfactory treatment has been reported so far (30). Neuronal apoptosis is believed to be one of the key events precipitating AD (31).…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's disease (AD), which is caused by the loss of neurons and synapse degeneration, is clinically characterized by changes in cognitive function ( 1 ), which affects >47 million people worldwide ( 2 ). Due to its complex pathological mechanism, its therapeutic targets have not yet been identified ( 3 ).…”
Section: Introductionmentioning
confidence: 99%